2012
DOI: 10.1120/jacmp.v13i6.3992
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and sensitivity of four‐dimensional dose calculation to systematic motion variability in stereotatic body radiotherapy (SBRT) for lung cancer

Abstract: The dynamic movement of radiation beam in real‐time tumor tracking may cause overdosing to critical organs surrounding the target. The primary objective of this study was to verify the accuracy of the 4D planning module incorporated in CyberKnife treatment planning system. The secondary objective was to evaluate the error that may occur in the case of a systematic change of motion pattern. Measurements were made using a rigid thorax phantom. Target motion was simulated with two waveforms (sin and cos4) of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…( 2 , 22 ) It has been demonstrated that target tracking techniques such as dynamic MLC tracking, robotic respiratory tracking, and tumor trailing strategy based on the moving average algorithm have the ability to adapt the baseline variation, but such adaptation is hardly reflected in the 4D dose calculation. Recently, Chan et al (23) have demonstrated that the sensitivity of 4D dose calculation to the variation of target motion differed by organs of interest in target‐tracking SBRT, with the greatest dosimetric errors observed in structures that were static or moved asynchronously with respect to the tracking object. Since planning risk volumes (PRV) have the limitations in serially functioning organs such as the spinal cord, (24) we suggest to simulate the intrafractional (and also interfractional) baseline drifts using the population data during treatment planning to avoid potential risks of overdosing these critical organs.…”
Section: Discussionmentioning
confidence: 99%
“…( 2 , 22 ) It has been demonstrated that target tracking techniques such as dynamic MLC tracking, robotic respiratory tracking, and tumor trailing strategy based on the moving average algorithm have the ability to adapt the baseline variation, but such adaptation is hardly reflected in the 4D dose calculation. Recently, Chan et al (23) have demonstrated that the sensitivity of 4D dose calculation to the variation of target motion differed by organs of interest in target‐tracking SBRT, with the greatest dosimetric errors observed in structures that were static or moved asynchronously with respect to the tracking object. Since planning risk volumes (PRV) have the limitations in serially functioning organs such as the spinal cord, (24) we suggest to simulate the intrafractional (and also interfractional) baseline drifts using the population data during treatment planning to avoid potential risks of overdosing these critical organs.…”
Section: Discussionmentioning
confidence: 99%
“…[15] On the contrary, our group has performed experimental investigations of the intrafractional target motion for the CyberKnife focusing on the RTS. [16,17] While it is hypothesized that XST based lung tumor treatment may be beneficial for a subset of patients who are medically inoperable, unsuitable for invasive fiducial implantation and whose tumors are not visible on the x-ray tracking system or attached to the vertebral column with limited motion range, experimental evaluations of this delivery technique have never been reported despite its increasing clinical applications. [18][19][20] In this study, we aimed to evaluate the adequacy of using the XLS-based strategy by studying the dose delivered to a moving tumor.…”
Section: Introductionmentioning
confidence: 98%
“…14 Chan et al have performed experimental investigations of the intrafractional target motion during CyberKnife treatment, focusing on real-time tracking and XST. [15][16][17] However, the influence of beam sizes and that of the interplay effect have not been experimentally studied.…”
Section: Introductionmentioning
confidence: 99%